Letter
034-0135-001 INTERNATIONAL BRIGADE Dependants and Wounded Aid Committee Patrons: Harry Adams The Duchess of Atholl, MP. H.N. Brailsford Seymour Cocks, MP Ebby Edwards Prof. J.B.S. Haldane. F.R.S. Oliver Harris Will Lawther Sir Walter Layton Earl of Listowel Sir Peter Chalmers Mitchell, C.B.E.. F.R.S., F.Z.S.. D.Sc LL.D. J.B. Priestley Eleanor Rathbone, M.P. Ald. J. Reeves E. Shinwell, M.P. W.J.R. Squance G.R. Strauss, M.P. Wilfrid Roberts, M.P. Ellen Wilkinson. M.P. Hon Secretary: CHARLOTTE HALDANE Telephone: Temple Bar 0178 1 LITCHFIELD STREET, LONDON, W.C.2. September 30th, 1938. Sir Walter Citrine, Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Sir Walter, We have just heard from the General Secretary of the Electrical Trade Union that his Executive Council made a grant of £100 to our Fund. He informs us that this money was sent to the International Solidarity Fund, earmarked for the Dependants and Wounded Aid Committee. As we are in urgent need of money at the moment, to provide for wounded men who are expected home soon, we would like to receive this £100 as soon as possible. With best wishes, Yours sincerely, INTERNATIONAL BRIGADE DEPENDANTS & WOUNDED AID COMMITTEE 292/946/34/135